Fire effects on plant reproductive fitness vary among individuals, reflecting pollination‐dependent mechanisms. Issue 4 (17th April 2023) - Richardson, Lea K.; Beck, Jared; Eck, Daniel J.; Shaw, Ruth; Wagenius, Stuart
Abstract: Premise: Fire induces flowering in many plant species worldwide, potentially improving reproductive fitness via greater availability of resources, as evident by flowering effort, and improved pollination outcomes, as evident by seed set. Postfire increases in flowering synchrony, and thus mating opportunities, may improve pollination. However, few studies evaluate fire effects on multiple components of fitness. Consequently, the magnitude and mechanism of fire effects on reproductive fitness remain unclear. Methods: Over multiple years and prescribed burns in a prairie preserve, we counted flowering stems, flowers, fruits, and seeds of three prairie perennials, Echinacea angustifolia, Liatris aspera, and Solidago speciosa . We used aster life‐history models to assess how fire and mating opportunities influenced annual maternal fitness and its components in individual plants. Results: In Echinacea and Liatris, but not in Solidago, fire increased head counts, and both fire and mating opportunities increased maternal fitness. Burned Echinacea and Liatris plants with many flower heads produced many seeds despite low seed set (fertilization rates). In contrast, plants with an average number of flower heads had high seed set and produced many seeds only when mating opportunities were abundant. Conclusions: Fire increased annual reproductive fitness via resource‐ and pollination‐dependent mechanisms in Echinacea and Liatris but did not affect Solidago fitness. The consistent relationship between synchrony and seed set implies that temporal mating opportunities play an important role in pollination. While fire promotes flowering in many plant species, our results reveal that even closely related species exhibit differential responses to fire, which could impact the broader plant community.